2000
DOI: 10.1159/000039760
|View full text |Cite
|
Sign up to set email alerts
|

Three Gaucher-Disease-Producing Mutations in a Patient with Gaucher Disease: Mechanism and Diagnostic Implications

Abstract: As Gaucher disease is an autosomal recessive disorder, most patients are either homozygotes or compound heterozygotes for glucocerebrosidase mutations. We have encountered a patient with three mutations, two c.1226A→G (1226G, N370S) and one c.1448 T→C (1448C, L444P). This was shown to be due to a gene conversion event in which the sequence of the glucocerebrosidase pseudogene that includes the 1448C mutation had been imposed on a glucocerebrosidase gene that already had the 1226G mutation. The patient had rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Patients heterozygous or homozygous for this mutation do not manifest Type 2 GD. There has, however, been at least one report where Asn370Ser (Asn409Ser) was found on the same allele in cis with another GBA1 mutation, which can further confuse the picture [16]. In contrast, the mutation Leu444Pro (Leu483Pro) is frequently encountered in Type 2 GD, although it is rare to identify patients who are homozygous.…”
Section: Genotype/phenotype Correlationmentioning
confidence: 99%
“…Patients heterozygous or homozygous for this mutation do not manifest Type 2 GD. There has, however, been at least one report where Asn370Ser (Asn409Ser) was found on the same allele in cis with another GBA1 mutation, which can further confuse the picture [16]. In contrast, the mutation Leu444Pro (Leu483Pro) is frequently encountered in Type 2 GD, although it is rare to identify patients who are homozygous.…”
Section: Genotype/phenotype Correlationmentioning
confidence: 99%
“…In 2000, Beutler and colleagues first reported an affected GD1 patient with three mutations, the c.1226A>G(p.N370S) missense mutation on one allele and the c.1226A> G(p.N370S) and c.1448T>C(p.L444P) missense mutations on the other (Beutler et al 2000). They recognized the implications for a false-positive prenatal diagnosis for such patients if the fetus had inherited the c.1226A>G(p.N370S)–c.1448C>T(p.L444P) allele and was diagnosed as affected, but was actually a GD heterozygote.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, Beutler et al described a patient with genotype N370S/ N370S who also carried mutation L444P [19]. Additionally, Filcamo et al reported a patient, with GD2 and genotype G202R/G202R (p.G241Rp./G241R), who also carried M361I (M400I) [8].…”
mentioning
confidence: 99%